Design of intelligent vehicular and sensor communication network: a comprehensive survey - Arslan Ahmed Amin; Ansa Mubarak; Habib Ulla Manzoor (Systems Science & Control Engineering, 2025)
This review paper provides a comprehensive review of Intelligent Vehicular and Sensor Communication Networks (IVSCN), focusing on the design details and recent advancements required to develop modern vehicular systems. It highlights the comprehensive sensor technologies such as Radar, Light Detection and Ranging (LiDAR), Cameras, and Ultrasonic sensors that aim to collect and synchronize data for vehicle operation and safety. The paper also critically assesses sophisticated network designs and architectures that strengthen vehicular communications. Further in-depth analysis is provided about vehicular network communication protocols and navigation systems, which can manage a multitude of traffic scenarios, including signal control, accidents, and congestion, which are invaluable for optimizing vehicle movement and ensuring road safety. Moreover, the review further covers practical applications and cases, demonstrating that these technologies have worked well, from providing sound traffic management systems to improving vehicle safety and environmental sustainability. The review also explores other Artificial Intelligence (AI) techniques used in fault-tolerant and intelligent communication methods, such as Kalman Filters, Particle Filters, and Fuzzy Logic Fusion. This literature review highlights the role of ongoing innovation in routing protocols, navigation systems, and data analytics; it thus has practical implications for both upcoming and well-known researchers.